Impact of Ghana's agricultural mechanization services center program - Benin, Samuel (Wiley, 2015)
Use of mechanization in African agriculture has returned strongly to the development agenda, particularly following the recent high food prices crisis. Many developing country governments—including Ghana, the case study of this article—have resumed support for agricultural mechanization, typically in the form of subsidies for tractor purchase and establishment of private‐sector‐run agricultural mechanization service centers (AMSECs). The aim of this article is to assess the impact of Ghana's AMSEC program on various farm household outcomes, using data from surveys that were conducted with 270 farm households. A two‐stage propensity score matching and difference‐in‐difference estimation procedure is used to estimate the impacts of the program, employing different definitions of treatment, model specifications, and matching algorithms to assess sensitivity of the estimator to different assumptions. The results indicate that the AMSEC program has had a mixed impact on different outcome indicators. For example, whereas the program has contributed to improving availability of mechanization services, reducing drudgery, and raising yield, it has had no impact on the change in the prices paid by farmers for the services used and the change in the amount of area plowed. Implications of the results on labor‐mechanization substitution and for raising and sustaining productivity further are drawn.